Investigation of fly ash properties with purpose of its utilization as a secondary raw material for portland cement clinker production - Baščarević Zvezdana; Komljenović Miroslav; Petrašinović-Stojkanović Ljiljana; Jovanović Nataša; Rosić Aleksandra; Ršumović Mihailo (Hemijska Industrija, 2006)
In this paper the results of the investigated properties of fly ash from four thermal power plants in Serbia are presented. The physical, chemical, mineralogical and thermal characterization of fly ash was carried out, in order to determine the possibility to utilize this material in the building materials industry, foremost in the cement industry. It was determined that, although there are differences concerning the physical, chemical, and mineralogical characteristics of the investigated samples, they are very similar concerning their thermal characteristics. It was concluded that using fly ash as one of the raw components in the mixture for Portland cement clinker synthesis, not only enables the substitution of natural resources, but it might have a positive effect on the lowering of the sintering temperature.